2016
DOI: 10.1107/s2059798316003351
|View full text |Cite
|
Sign up to set email alerts
|

RNA protects a nucleoprotein complex against radiation damage

Abstract: Radiation damage during macromolecular X-ray crystallographic data collection is still the main impediment for many macromolecular structure determinations. Even when an eventual model results from the crystallographic pipeline, the manifestations of radiation-induced structural and conformation changes, the so-called specific damage, within crystalline macromolecules can lead to false interpretations of biological mechanisms. Although this has been well characterized within protein crystals, far less is known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Recently nucleic acids in DNA-protein and RNA-protein complex crystals have been shown to be significantly more durable and robust to radiation, but they do suffer from the cleavage of base sugar nitrogen-carbon and sugar-phosphate carbon-oxygen bonds [82,83].…”
Section: Structure Solution and Interpretationmentioning
confidence: 99%
“…Recently nucleic acids in DNA-protein and RNA-protein complex crystals have been shown to be significantly more durable and robust to radiation, but they do suffer from the cleavage of base sugar nitrogen-carbon and sugar-phosphate carbon-oxygen bonds [82,83].…”
Section: Structure Solution and Interpretationmentioning
confidence: 99%
“…For nucleic acid crystallography, radiation damage, while a critically important factor, may not be as serious as it is for protein S-SAD. A recent study of a nucleoprotein complex [109] quantified the per-atom electron density changes over a wide range of radiation dose levels (1.3-25.0 MGy) and showed that RNA is much less sensitive to radiation-induced chemical changes than protein. And, unexpectedly, the normally radiation sensitive Glu and Asp residues within RNA binding pockets appear to have been protected by the association with RNA.…”
Section: Radiation Damagementioning
confidence: 99%
“…In this work, we will outline how specific damage events in crystallographic models can be interpreted in terms of local structural deformations caused by the population and depopulation of virtual and occupied electronic states in the close vicinity of the Fermi energy of the perfect crystal. Previous reports in the literature have addressed and quantified the local changes, but unfortunately, due to the lack of a unifying model, a quantification of this effect has proved to be very subjective and system dependent (although procedures for radiation damage corrections have been refined empirically to a point where a systematic and automated assessment is possible [1,5,15]). It is our view that single crystal macromolecular crystallography oscillation datasets are unsuitable for assessing the structural changes caused by specific damage, since they rely on information obtained too long (seconds) after the initial interaction of the X-ray beam with the sample.…”
Section: Introductionmentioning
confidence: 99%